Structural investigations of tungsten silver phosphate glasses by solid state NMR, vibrational and X-ray absorption near edge spectroscopies - Santagneli, Silvia H. [UNESP]; Poirier, Gael; Rinke, Matthias T.; Ribeiro, Sidney José Lima [UNESP]; Messaddeq, Younes [UNESP]; Eckert, Hellmut (Elsevier B.V., 2011)
Glasses were prepared in the pseudo-binary system (1 - x)AgPO(3)-xWO(3) (0 <= x <= 0.6 mol%). The structural evolution of the vitreous network was studied as a function of composition by thermal analysis, Fourier Transform Infrared spectroscopy (FTIR). Raman scattering, high resolution (31)P solid state NMR and XANES at the W-L(1) absorption edge. For compositions with x ranging from 0 to 0.5 a pronounced increase in the glass transition temperature is observed, suggesting a significant increase in the glass network connectivity. At the same time Raman spectra indicate that tungsten atoms are linked to non-bridging oxygen atoms (W-O- or W=O bonded species) whereas the (31)P MAS-NMR spectra indicate the successive formation of new P-O-W linkages. The formation of some anionic tungsten sites (if these are revealed by the presence of W-O terminal bonds) implies an increase in the average degree of polymerization of the phosphate network, which is consistent with the compositional evolution of the (31)P MAS-NMR spectra at low x values. For higher x-values. the Raman spectra indicate the presence of W-O-W linkages. W-L(1) XANES data indicate that at least 90% of tungsten atoms are octahedrally coordinated. (c) 2011 Elsevier B.V. All rights reserved.
Keywords: Tungstate glasses; Glass structure; Solid state NMR; Raman; XANES